2007
DOI: 10.1130/g23288a.1
|View full text |Cite
|
Sign up to set email alerts
|

Sediment delivery after a wildfire

Abstract: We use a record of sedimentation in a small reservoir within the Cerro Grande burn area, New Mexico, to document postfi re delivery of ash, other fi ne-grained sediment carried in suspension within fl oods, and coarse-grained sediment transported as bedload over a fi ve-year period. Ash content of sediment layers is estimated using fallout 137 Cs as a tracer, and ash concentrations are shown to rapidly decrease through a series of moderate-intensity convective storms in the fi rst rainy season after the fi re.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 15 publications
5
108
0
1
Order By: Relevance
“…Some estimates have been made by measuring the rate of sedimentation in water impoundments. These studies have been conducted in pine plantations in South Africa (Scott and Van Wyk, 1990), and coniferous forests in Colorado (Moody and Martin, 2001a,b) and New Mexico (Lavine et al, 2006;Reneau et al, 2007). During the first year after fire, Scott et al (1998) and Scott and Van Wyk (1990) reported a fourfold increase in bedload export, with 30% of the total sediment exported being bedload.…”
Section: The Role Of Coarse Matter In Total Phosphorus Stream Exportsmentioning
confidence: 94%
See 1 more Smart Citation
“…Some estimates have been made by measuring the rate of sedimentation in water impoundments. These studies have been conducted in pine plantations in South Africa (Scott and Van Wyk, 1990), and coniferous forests in Colorado (Moody and Martin, 2001a,b) and New Mexico (Lavine et al, 2006;Reneau et al, 2007). During the first year after fire, Scott et al (1998) and Scott and Van Wyk (1990) reported a fourfold increase in bedload export, with 30% of the total sediment exported being bedload.…”
Section: The Role Of Coarse Matter In Total Phosphorus Stream Exportsmentioning
confidence: 94%
“…A large increase in P concentration was measured in North Carolinian river when increased flow produced turbulence, which resuspended stream bed material (Keup, 1968). As residence timing of coarse material in streams exceeds that of suspended matter (Reneau et al, 2007), increased P concentrations have the potential to be more sustained, extending the impact of wildfire.…”
Section: The Role Of Coarse Matter In Total Phosphorus Stream Exportsmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study of its kind in North America, although FRNs have been used qualitatively in New Mexico, USA to investigate the effect of wildfires on ash redistribution and FRN depth profiles in soils (e.g. Johansen et al 2003;Reneau et al 2007). Recent Australian studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the snowmelt-derived sediment transport increases are the result of the sustained (i.e. 1 to 4 month) delivery of water to channels, which leads to transport of coarse-grained sediment as bedload (Moody and Martin, 2001;Malmon et al, 2004;Reneau et al, 2007). Elevated streamflow from snowmelt in burned areas can also impact stream channels by increasing nutrient export, removing periphyton, and altering benthic macroinvertebrate assemblages (Minshall et al, 2001).…”
Section: Motivation and Previous Researchmentioning
confidence: 99%